2017
DOI: 10.1007/s00234-017-1782-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of deep gray matter volume, cortical thickness and white matter integrity in patients with typical absence epilepsy: a study using voxelwise-based techniques

Abstract: Abnormalities found in white matter integrity may help to better understand the pathophysiology of AE and optimize diagnosis and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
6
1
1
Order By: Relevance
“…(B) Afferent and efferent fibers of the dentate nucleus. matter abnormalities in patients with temporal lobe epilepsy (Rodríguez-Cruces and Concha, 2015) and absence epilepsy (Correa et al, 2017). The present experimental study showed the absence of or weak dento-thalamic connections in GAERS, which may have a role in the pathophysiology of absence seizures.…”
Section: Fig 2 (A)supporting
confidence: 49%
“…(B) Afferent and efferent fibers of the dentate nucleus. matter abnormalities in patients with temporal lobe epilepsy (Rodríguez-Cruces and Concha, 2015) and absence epilepsy (Correa et al, 2017). The present experimental study showed the absence of or weak dento-thalamic connections in GAERS, which may have a role in the pathophysiology of absence seizures.…”
Section: Fig 2 (A)supporting
confidence: 49%
“…Previously, CAE studies using diffusion-weighted MRI reported lower fractional anisotropy (FA) values in the genu, an important part of the corpus callosum in the frontal lobe. 6,39 However, although diffusion-weighted MRI measures are valuable in white matter research, they fail to provide more specific information on the myelin content and cannot discriminate between axonal damage, alterations in myelin content, or topographic deviations. 40 Previously, Spader et al 41 showed the feasibility of identifying in vivo myelin abnormalities using MRI and reported a reduced MWF in three children with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced neuroimaging techniques, such as DTI (diffusion tensor imaging) tractography have disclosed white matter tracts and bundles abnormalities in IGEs [2]. Thalamic and corpus callosum abnormalities have been described in IGE patients presenting predominately with absence seizures.…”
Section: Introductionmentioning
confidence: 99%